Iron-based ceramic composite reinforced wear-resistant material manufactured by vacuum infiltration method and preparation method of iron-based ceramic composite reinforced wear-resistant material

Through vacuum impregnation method and multi-step process processing, the problem of difficult balance between strength, toughness and wear resistance of existing iron-based ceramic materials is solved, and the performance coordination of the material and corrosion resistance are improved.

CN119392086AActive Publication Date: 2025-02-07BEIDOU (TIANJIN) NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411424149.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-07
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing iron-based ceramic materials are difficult to balance and coordinate between strength, toughness and wear resistance, and the corrosion resistance and cold and hot impact stability are insufficient, which limits the efficiency of the product.

Method used

The iron-based ceramic composite material is manufactured by vacuum impregnation method, and the porous structure is formed by mixing and sintering the ceramic particles with binders, activators, and paraffin particles. The impregnation kinetic energy of the iron-based alloy liquid is enhanced by vacuum negative pressure to improve the The bonding strength of the material and the modified ceramic particles and enhancers are improved by irradiation and ultrasonic immersion.

Benefits of technology

The coordinated improvements between the strength, toughness and wear resistance of iron-based ceramic composite materials are achieved, the corrosion resistance and cold impact stability of the material are improved, and the overall performance and use efficiency of the product are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081681300000151
    Figure BDA0005081681300000151
  • Figure BDA0005081681300000161
    Figure BDA0005081681300000161
  • Figure BDA0005081681300000162
    Figure BDA0005081681300000162
Patent Text Reader

Abstract

The invention relates to the technical field of iron-based ceramic composite materials, in particular to an iron-based ceramic composite reinforced wear-resistant material manufactured through a vacuum infiltration method and a preparation method of the iron-based ceramic composite reinforced wear-resistant material. The preparation method comprises the following steps that ceramic particles with the particle size being 0.8-2.2 mm, a binder, an activating agent and paraffin particles are mixed and stirred according to the proportion to be prepared into a mixture; the stirred mixture is placed in a mold of a ceramic precast block for compression molding, and then the mold is placed in a resistance furnace; according to the iron-based ceramic composite reinforced wear-resistant material, ceramic particles, a binder, an activating agent and paraffin particles are mixed according to a certain ratio, compression molding is performed, sintering treatment is performed in a resistance furnace, a ceramic precast block of a porous structure is formed, and high-temperature iron-based alloy liquid is vacuumized to be matched and infiltrated into pores of a ceramic precast body, so that the wear-resistant material is obtained. The formed composite reinforced wear-resistant material has coordinated improvement of strength, toughness and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of iron-based ceramic composite materials, and in particular to an iron-based ceramic composite reinforced wear-resistant material manufactured by a vacuum infiltration method and a preparation method thereof. Background Art

[0002] The application and research of wear-resistant materials play an important role in today's industrial development, such as mechanical equipment in cement, machinery, electricity, mining, metallurgy, shipbuilding, chemical and coal industries, grinding balls, grinding discs, grinding rollers and accessories of various mills, as well as crushing walls, crushing plates, and impact crusher hammers of crushers.

[0003] The strength, toughness and wear resistance of existing iron-based ceramic materials are difficult to improve in a balanced and coordinated manner. Improving the balance between the performances is the technical difficulty of the present invention. At the same time, the corrosion resistance and thermal shock stability of the product are poor, which further limits the efficiency of the product. Based on this, the present invention further improves it. Summary of the invention

[0004] In view of the defects of the prior art: 1. The air in the pores of the ceramic prefabricated block is forced to be discharged, solving the problem that it is difficult to discharge naturally. 2. The pressure formed by the vacuum negative pressure enhances the infiltration kinetic energy of the infiltrating iron-based alloy liquid, thereby improving the bonding strength of the composite material. 3. The molten iron components are purified by the negative pressure environment to improve the purity of the molten iron of the iron-based alloy. The purpose of the present invention is to provide a vacuum infiltration method for manufacturing iron-based ceramic composite reinforced wear-resistant materials and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a method for preparing an iron-based ceramic composite reinforced wear-resistant material by a vacuum infiltration method, comprising the following steps:

[0007] Step 1: Ceramic particles with a particle size of 0.8-2.2 mm are mixed with a binder, an activator, and paraffin particles in proportion and stirred to form a mixture;

[0008] Step 2: placing the mixture stirred in step 1 in a ceramic prefabricated block mold for pressing, then placing the mold in a resistance furnace, heating it to 120° C., demolding it after 2 hours, and then sintering it at a high temperature of 1250° C. for 12 hours to make it undergo a phase change, and naturally cooling it to room temperature to obtain a ceramic prefabricated block with a porous structure;

[0009] Step 3: Place the ceramic prefabricated block in the formed membrane shell, preheat it to 450-850°C, and then place the preheated membrane shell in a vacuum furnace;

[0010] Step 4: heating the iron-based alloy to 1520-1550° C., melting to form a high-temperature iron-based alloy liquid, and pouring it into the membrane shell of the vacuum furnace, closing the sealing cover of the vacuum furnace to keep it in a closed state, and starting the vacuum pump to evacuate the air in the vacuum furnace to a vacuum state, so that the air in the pores of the ceramic prefabricated block is evacuated, thereby allowing the iron-based alloy liquid to infiltrate the pores of the ceramic prefabricated body, keeping the temperature for 16-24 hours, and then cooling to room temperature to obtain the composite reinforced wear-resistant material of the present invention;

[0011] The iron-based alloy comprises the following raw materials in parts by weight: 2-3.5 parts of C, 10-30 parts of Cr, 70-75 parts of Fe, 1.5-2 parts of Mo, and 1.5-2 parts of V.

[0012] Preferably, the ratio of the ceramic particles to the binder, the activator, and the paraffin particles is (8-11):(2-3):(1-3):1; wherein the activator is one of aluminum powder, silicon carbide powder, and tungsten carbide powder; and the binder is an inorganic binder;

[0013] The porosity of the ceramic prefabricated block with a porous structure is 35-60%; the membrane shell preheated for molding is made of metal heat-resistant steel.

[0014] Preferably, the composite reinforced wear-resistant material further comprises 8-13 parts of a reinforcing agent; the reinforcing agent is used for reinforcing and improving the iron-based alloy;

[0015] The preparation method of the enhancer is as follows:

[0016] S01: irradiate the yttrium oxide in a proton irradiation box for 5-10 minutes at a power of 350W. After the irradiation is completed, preheat the yttrium oxide at 55-60°C for 10-15 minutes to obtain a preheated yttrium oxide body.

[0017] S02: Blend 2-4 parts of silane coupling agent KH550, 1-3 parts of chitosan solution with a mass fraction of 2-5%, and 4-7 parts of sodium dodecylbenzene sulfonate solution thoroughly;

[0018] Then, 3-5 parts of preheated yttrium oxide and 2-4 parts of B powder are added, and the blending and ball milling treatment is continued. The ball milling speed is 1500r / min, and the ball milling is performed for 2h. After the ball milling is completed, a yttrium oxide-based modifier is obtained;

[0019] S03: placing Si powder in a dopamine hydrochloride solution with an amount of 3-5 times the total amount of Si powder, and then adding carboxymethyl cellulose with an amount of 5-8% of the total amount of Si powder and blending them thoroughly to obtain a regulator;

[0020] S04: The regulator and the yttrium oxide-based modifier are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water and dried to obtain a reinforcing agent.

[0021] Preferably, the mass fraction of the sodium dodecylbenzenesulfonate solution is 3-6%; the mass fraction of the dopamine hydrochloride solution is 4-7%.

[0022] Preferably, the particle size of the B powder is 10-15 um; the particle size of the Si powder is 2-5 um; the stirring speed of the stirring modification treatment is 450-550 r / min, and the stirring time is 30-40 min.

[0023] Preferably, the preparation method of the iron-based alloy is:

[0024] The alloy containing C, Cr, Fe, Mo, V and the reinforcing agent are sequentially added into the smelting furnace for smelting to form an iron-based alloy melt, which is then cast into a mold, cooled and formed, and then demolded to obtain an iron-based alloy ingot.

[0025] Preferably, the ceramic particles are also treated by ultrasonic immersion of a modifier;

[0026] The preparation method of the modifier is:

[0027] S11: immersing the silicon carbide whiskers into a lanthanum nitrate solution having a mass fraction of 4-6% and a value 3-5 times the total amount of the silicon carbide whiskers;

[0028] Then, 5-8% of the total amount of silicon carbide whiskers is added with silane coupling agent KH560, and the mixture is immersed and stirred sufficiently. The immersion speed is 550-750 r / min, and the immersion time is 30 min. After the immersion is completed, a lanthanum-doped whisker liquid is obtained;

[0029] S12: 2-5 parts of hydroxyapatite, 1-3 parts of flake graphene, 3-6 parts of sodium lignin sulfonate solution, 1-3 parts of citric acid and 0.50-0.75 parts of nano-silica sol are mixed and ball-milled at a speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified additive;

[0030] S13: The lanthanum-doped whisker liquid and the modifying additive are mixed in a weight ratio of 7:3 to obtain a modifying agent.

[0031] Preferably, the mass fraction of the sodium lignin sulfonate solution is 2-5%;

[0032] Preferably, the immersion power of the ultrasonic immersion treatment is 350-400W, and the immersion time is 20-30min;

[0033] The invention also provides a composite reinforced wear-resistant material prepared by a method for preparing an iron-based ceramic composite reinforced wear-resistant material by a vacuum infiltration method.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. The iron-based ceramic composite reinforced wear-resistant material of the present invention adopts ceramic particles, a binder, an activator, and paraffin particles to be mixed in a certain ratio, and then pressed and formed, and then sintered in a resistance furnace to form a ceramic prefabricated block with a porous structure. The high-temperature iron-based alloy liquid is vacuumed and infiltrated into the pores of the ceramic prefabricated body. The formed composite reinforced wear-resistant material has coordinated improvement in strength, toughness and wear resistance; the iron-based alloy adopts C, Cr, Fe, Mo, and V as the matrix raw materials, and the reinforcing agent is coordinated and matched, and the synergistic effect between the raw materials is adopted. At the same time, the ceramic particles are also ultrasonically immersed in the modifier for further coordination, so that the performance of the product is further improved;

[0036] 2. The reinforcing agent is yttrium oxide, which is first placed in a proton irradiation box for 5-10 minutes, and the irradiation power is 350W. After the irradiation, it is preheated at 55-60°C for 10-15 minutes. The activity of yttrium oxide is stimulated by irradiation and preheating. At the same time, silane coupling agent KH550, chitosan solution with a mass fraction of 2-5%, sodium dodecylbenzene sulfonate solution, and B powder are blended and adjusted. The interface between the raw materials of the system is enhanced by the coordination and matching between the raw materials, and then a regulator is combined to enhance the synergy. The Si powder in the regulator is first placed in a dopamine hydrochloride solution, and then mixed with carboxymethyl cellulose to obtain a regulator. The Si powder in the regulator is used to blend B powder and yttrium oxide, and then processed by the special process of the present invention, so that the organization grains can be refined and the grain structure can be strengthened in the alloy system, thereby obtaining an iron-based alloy combined with a ceramic body, and the strength, toughness and wear resistance of the product are further coordinated and improved, and the corrosion resistance and cold and hot shock resistance of the product are further improved;

[0037] 3. The modifier is made of silicon carbide whiskers, lanthanum nitrate solution with a mass fraction of 4-6%, and silane coupling agent KH560. The interface between the raw materials is enhanced through the coordination between the raw materials. At the same time, the whisker-like structure of the silicon carbide whiskers is distributed in the system, which enhances the wetting and interface improvement of the modifier on the ceramic particles. At the same time, the modifier additives are combined to enhance the improvement effect of the modifier on the ceramic particles, so that the product performance is further improved;

[0038] 4. The modified additive is made of hydroxyapatite, flaky graphene, sodium lignin sulfonate solution, citric acid and nano-silica sol, which are fully blended and ball-milled. The point-shaped hydroxyapatite is combined with the flaky graphene, which can better attach the modifier system to the surface of the ceramic particles, facilitate the lanthanum element in the modifier to penetrate and enhance the efficiency of the ceramic particle system, strengthen the organizational structure, and at the same time, the performance effect of the modifier on the ceramic particle system is further improved through the coordination of the raw materials of the modified additive with the whisker structure, thereby further enhancing the performance of the iron-based ceramic composite reinforced wear-resistant material. DETAILED DESCRIPTION

[0039] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] The method for preparing an iron-based ceramic composite reinforced wear-resistant material by vacuum infiltration in this embodiment comprises the following steps:

[0041] Step 1: Ceramic particles with a particle size of 0.8-2.2 mm are mixed with a binder, an activator, and paraffin particles in proportion and stirred to form a mixture;

[0042] Step 2: placing the mixture stirred in step 1 in a ceramic prefabricated block mold for pressing, then placing the mold in a resistance furnace, heating it to 120° C., demolding it after 2 hours, and then sintering it at a high temperature of 1250° C. for 12 hours to make it undergo a phase change, and naturally cooling it to room temperature to obtain a ceramic prefabricated block with a porous structure;

[0043] Step 3: Place the ceramic prefabricated block in the formed membrane shell, preheat it to 450-850°C, and then place the preheated membrane shell in a vacuum furnace;

[0044] Step 4: heating the iron-based alloy to 1520-1550° C., melting to form a high-temperature iron-based alloy liquid, and pouring it into the membrane shell of the vacuum furnace, closing the sealing cover of the vacuum furnace to keep it in a closed state, and starting the vacuum pump to evacuate the air in the vacuum furnace to a vacuum state, so that the air in the pores of the ceramic prefabricated block is evacuated, thereby allowing the iron-based alloy liquid to infiltrate the pores of the ceramic prefabricated body, keeping the temperature for 16-24 hours, and then cooling to room temperature to obtain the composite reinforced wear-resistant material of the present invention;

[0045] The iron-based alloy comprises the following raw materials in parts by weight: 2-3.5 parts of C, 10-30 parts of Cr, 70-75 parts of Fe, 1.5-2 parts of Mo, and 1.5-2 parts of V.

[0046] The ratio of the ceramic particles to the binder, activator, and paraffin particles in this embodiment is (8-11): (2-3): (1-3): 1; wherein the activator is one or more of aluminum powder, silicon carbide powder, and tungsten carbide powder; the binder is an inorganic binder, and the inorganic binder is attapulgite clay;

[0047] The porosity of the ceramic prefabricated block with a porous structure is 35-60%; the membrane shell preheated for forming is made of metal heat-resistant steel, non-metal and composite material.

[0048] The composite reinforced wear-resistant material of this embodiment also includes 8-13 parts of a reinforcing agent; the reinforcing agent is used for reinforcing and improving the iron-based alloy;

[0049] The preparation method of the enhancer is as follows:

[0050] S01: irradiate the yttrium oxide in a proton irradiation box for 5-10 minutes at a power of 350W. After the irradiation is completed, preheat the yttrium oxide at 55-60°C for 10-15 minutes to obtain a preheated yttrium oxide body.

[0051] S02: Blend 2-4 parts of silane coupling agent KH550, 1-3 parts of chitosan solution with a mass fraction of 2-5%, and 4-7 parts of sodium dodecylbenzene sulfonate solution thoroughly;

[0052] Then, 3-5 parts of preheated yttrium oxide and 2-4 parts of B powder are added, and the blending and ball milling treatment is continued. The ball milling speed is 1500r / min, and the ball milling is performed for 2h. After the ball milling is completed, a yttrium oxide-based modifier is obtained;

[0053] S03: placing Si powder in a dopamine hydrochloride solution with an amount of 3-5 times the total amount of Si powder, and then adding carboxymethyl cellulose with an amount of 5-8% of the total amount of Si powder and blending them thoroughly to obtain a regulator;

[0054] S04: The regulator and the yttrium oxide-based modifier are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water and dried to obtain a reinforcing agent.

[0055] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 3-6%; the mass fraction of the dopamine hydrochloride solution is 4-7%.

[0056] The particle size of the B powder in this embodiment is 10-15um; the particle size of the Si powder is 2-5um; the stirring speed of the stirring modification treatment is 450-550r / min, and the stirring time is 30-40min.

[0057] The preparation method of the iron-based alloy of this embodiment is:

[0058] The alloy containing C, Cr, Fe, Mo, V and the reinforcing agent are sequentially added into the smelting furnace for smelting to form an iron-based alloy melt, which is then cast into a mold, cooled and formed, and then demolded to obtain an iron-based alloy ingot.

[0059] The ceramic particles of this embodiment are also treated by ultrasonic immersion of the modifier;

[0060] The preparation method of the modifier is:

[0061] S11: immersing the silicon carbide whiskers into a lanthanum nitrate solution having a mass fraction of 4-6% and a value 3-5 times the total amount of the silicon carbide whiskers;

[0062] Then, 5-8% of the total amount of silicon carbide whiskers is added with silane coupling agent KH560, and the mixture is immersed and stirred sufficiently. The immersion speed is 550-750 r / min, and the immersion time is 30 min. After the immersion is completed, a lanthanum-doped whisker liquid is obtained;

[0063] S12: 2-5 parts of hydroxyapatite, 1-3 parts of flake graphene, 3-6 parts of sodium lignin sulfonate solution, 1-3 parts of citric acid and 0.50-0.75 parts of nano-silica sol are mixed and ball-milled at a speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified additive;

[0064] S13: The lanthanum-doped whisker liquid and the modifying additive are mixed in a weight ratio of 7:3 to obtain a modifying agent.

[0065] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2-5%;

[0066] The immersion power of the ultrasonic immersion treatment in this embodiment is 350-400W, and the immersion time is 20-30min;

[0067] The composite reinforced wear-resistant material prepared by the method for preparing an iron-based ceramic composite reinforced wear-resistant material by a vacuum infiltration method in this embodiment.

[0068] Example 1.

[0069] The method for preparing an iron-based ceramic composite reinforced wear-resistant material by vacuum infiltration in this embodiment comprises the following steps:

[0070] Step 1: Ceramic particles with a particle size of 0.8 mm are mixed with a binder, an activator, and paraffin particles in proportion to form a mixture;

[0071] Step 2: placing the mixture stirred in step 1 in a ceramic prefabricated block mold for pressing, then placing the mold in a resistance furnace, heating it to 120° C., demolding it after 2 hours, and then sintering it at a high temperature of 1250° C. for 12 hours to make it undergo a phase change, and naturally cooling it to room temperature to obtain a ceramic prefabricated block with a porous structure;

[0072] Step 3: Place the ceramic prefabricated block in the formed membrane shell, preheat it to 450°C, and then place the preheated membrane shell in a vacuum furnace;

[0073] Step 4: heating the iron-based alloy to 1520° C. to melt and form a high-temperature iron-based alloy liquid, and pouring the liquid into the membrane shell of the vacuum furnace, closing the sealing cover of the vacuum furnace to keep it in a closed state, and starting the vacuum pump to evacuate the air in the vacuum furnace to a vacuum state, so that the air in the pores of the ceramic prefabricated block is evacuated, thereby allowing the iron-based alloy liquid to infiltrate the pores of the ceramic prefabricated body, and then cooling to room temperature after keeping the temperature for 16 hours to obtain the composite reinforced wear-resistant material of the present invention;

[0074] The iron-based alloy includes the following raw materials in parts by weight: 2 parts of C, 10 parts of Cr, 70 parts of Fe, 1.5 parts of Mo, and 1.5 parts of V.

[0075] The ratio of ceramic particles to binder, activator, and paraffin particles in this embodiment is 8:2:1:1; the activator is aluminum powder; and the binder is an inorganic binder;

[0076] The porosity of the ceramic prefabricated block with a porous structure is 35%; the membrane shell preheated for molding is made of metal heat-resistant steel.

[0077] The composite reinforced wear-resistant material of this embodiment also includes 8 parts of reinforcing agent; the reinforcing agent is used for reinforcing and improving the iron-based alloy;

[0078] The preparation method of the enhancer is as follows:

[0079] S01: yttrium oxide is first placed in a proton irradiation box for 5 minutes, the irradiation power is 350W, and then preheated at 55°C for 10 minutes. After the preheating is completed, a preheated yttrium oxide body is obtained;

[0080] S02: 2 parts of silane coupling agent KH550, 1 part of 2% chitosan solution by mass and 4 parts of sodium dodecylbenzene sulfonate solution are mixed thoroughly;

[0081] Then, 3 parts of preheated yttrium oxide and 2 parts of B powder were added, and the blending and ball milling treatment was continued. The ball milling speed was 1500r / min, and the ball milling was performed for 2h. After the ball milling was completed, a yttrium oxide-based modifier was obtained.

[0082] S03: Si powder is first placed in a dopamine hydrochloride solution with an amount of 3 times the total amount of Si powder, and then carboxymethyl cellulose with an amount of 5% of the total amount of Si powder is added and mixed thoroughly to obtain a regulator;

[0083] S04: The regulator and the yttrium oxide-based modifier are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water and dried to obtain a reinforcing agent.

[0084] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 3%; the mass fraction of the dopamine hydrochloride solution is 4%.

[0085] The particle size of the B powder in this embodiment is 10 um; the particle size of the Si powder is 2 um; the stirring speed of the stirring modification treatment is 450 r / min, and the stirring time is 30 min.

[0086] The preparation method of the iron-based alloy of this embodiment is:

[0087] The alloy containing C, Cr, Fe, Mo, V and the reinforcing agent are sequentially added into the smelting furnace for smelting to form an iron-based alloy melt, which is then cast into a mold, cooled and formed, and then demolded to obtain an iron-based alloy ingot.

[0088] The ceramic particles of this embodiment are also treated by ultrasonic immersion of the modifier;

[0089] The preparation method of the modifier is:

[0090] S11: immersing the silicon carbide whiskers into a 4% lanthanum nitrate solution having a mass fraction of 3 times the total amount of the silicon carbide whiskers;

[0091] Then, 5% of the total amount of silicon carbide whiskers was added with silane coupling agent KH560, and the mixture was immersed and stirred sufficiently. The immersion speed was 550 r / min, and the immersion time was 30 min. After the immersion was completed, a lanthanum-doped whisker solution was obtained.

[0092] S12: 2 parts of hydroxyapatite, 1 part of flake graphene, 3 parts of sodium lignin sulfonate solution, 1 part of citric acid and 0.50 parts of nano-silica sol are mixed and ball-milled at a speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified additive;

[0093] S13: The lanthanum-doped whisker liquid and the modifying additive are mixed in a weight ratio of 7:3 to obtain a modifying agent.

[0094] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2%;

[0095] The immersion power of the ultrasonic immersion treatment in this embodiment is 350W, and the immersion time is 20min;

[0096] The composite reinforced wear-resistant material prepared by the method for preparing an iron-based ceramic composite reinforced wear-resistant material by a vacuum infiltration method in this embodiment.

[0097] Example 2.

[0098] The method for preparing an iron-based ceramic composite reinforced wear-resistant material by vacuum infiltration in this embodiment comprises the following steps:

[0099] Step 1: Ceramic particles with a particle size of 2.2 mm are mixed with a binder, an activator, and paraffin particles in proportion to form a mixture;

[0100] Step 2: placing the mixture stirred in step 1 in a ceramic prefabricated block mold for pressing, then placing the mold in a resistance furnace, heating it to 120° C., demolding it after 2 hours, and then sintering it at a high temperature of 1250° C. for 12 hours to make it undergo a phase change, and naturally cooling it to room temperature to obtain a ceramic prefabricated block with a porous structure;

[0101] Step 3: placing the ceramic prefabricated block in the formed membrane shell, preheating it to 850°C, and then placing the preheated membrane shell in a vacuum furnace;

[0102] Step 4: heating the iron-based alloy to 1550° C. to melt and form a high-temperature iron-based alloy liquid, and pouring the high-temperature iron-based alloy liquid into the membrane shell of the vacuum furnace, closing the sealing cover of the vacuum furnace to keep it in a closed state, and starting the vacuum pump to evacuate the air in the vacuum furnace to a vacuum state, so that the air in the pores of the ceramic prefabricated block is evacuated, thereby allowing the iron-based alloy liquid to infiltrate the pores of the ceramic prefabricated body, and then cooling to room temperature after keeping warm for 24 hours to obtain the composite reinforced wear-resistant material of the present invention;

[0103] The iron-based alloy includes the following raw materials in parts by weight: 3.5 parts of C, 30 parts of Cr, 75 parts of Fe, 2 parts of Mo, and 2 parts of V.

[0104] The ratio of ceramic particles to binder, activator, and paraffin particles in this embodiment is 11:3:3:1; the activator is aluminum powder; and the binder is an inorganic binder;

[0105] The porosity of the ceramic prefabricated block with a porous structure is 60%; the membrane shell preheated for molding is made of metal heat-resistant steel.

[0106] The composite reinforced wear-resistant material of this embodiment also includes 3 parts of reinforcing agent; the reinforcing agent is used for reinforcing and improving the iron-based alloy;

[0107] The preparation method of the enhancer is as follows:

[0108] S01: yttrium oxide is first placed in a proton irradiation box for 10 minutes, the irradiation power is 350W, and then preheated at 60°C for 15 minutes. After the preheating is completed, a preheated yttrium oxide body is obtained;

[0109] S02: Blend 4 parts of silane coupling agent KH550, 3 parts of 5% chitosan solution by mass and 7 parts of sodium dodecylbenzene sulfonate solution thoroughly;

[0110] Then, 5 parts of preheated yttrium oxide and 4 parts of B powder were added, and the blending and ball milling treatment was continued. The ball milling speed was 1500r / min, and the ball milling was performed for 2h. After the ball milling was completed, a yttrium oxide-based modifier was obtained.

[0111] S03: Si powder is first placed in a dopamine hydrochloride solution with an amount of 5 times the total amount of Si powder, and then carboxymethyl cellulose with an amount of 8% of the total amount of Si powder is added and mixed thoroughly to obtain a regulator;

[0112] S04: The regulator and the yttrium oxide-based modifier are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water and dried to obtain a reinforcing agent.

[0113] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 6%; the mass fraction of the dopamine hydrochloride solution is 7%.

[0114] The particle size of the B powder in this embodiment is 15 um; the particle size of the Si powder is 5 um; the stirring speed of the stirring modification treatment is 550 r / min, and the stirring time is 40 min.

[0115] The preparation method of the iron-based alloy of this embodiment is:

[0116] The alloy containing C, Cr, Fe, Mo, V and the reinforcing agent are sequentially added into the smelting furnace for smelting to form an iron-based alloy melt, which is then cast into a mold, cooled and formed, and then demolded to obtain an iron-based alloy ingot.

[0117] The ceramic particles of this embodiment are also treated by ultrasonic immersion of the modifier;

[0118] The preparation method of the modifier is:

[0119] S11: immersing the silicon carbide whiskers into a 6% lanthanum nitrate solution having a mass fraction of 5 times the total amount of the silicon carbide whiskers;

[0120] Then, 8% of the total amount of silicon carbide whiskers was added with silane coupling agent KH560, and the mixture was immersed and stirred sufficiently. The immersion speed was 750 r / min, and the immersion time was 30 min. After the immersion was completed, a whisker solution doped with lanthanum was obtained.

[0121] S12: 5 parts of hydroxyapatite, 3 parts of flake graphene, 6 parts of sodium lignin sulfonate solution, 3 parts of citric acid and 0.75 parts of nano-silica sol are mixed and ball-milled at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified additive;

[0122] S13: The lanthanum-doped whisker liquid and the modifying additive are mixed in a weight ratio of 7:3 to obtain a modifying agent.

[0123] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5%;

[0124] The immersion power of the ultrasonic immersion treatment in this embodiment is 400W, and the immersion time is 30min;

[0125] The composite reinforced wear-resistant material prepared by the method for preparing an iron-based ceramic composite reinforced wear-resistant material by a vacuum infiltration method in this embodiment.

[0126] Example 3.

[0127] The method for preparing an iron-based ceramic composite reinforced wear-resistant material by vacuum infiltration in this embodiment comprises the following steps:

[0128] Step 1: Ceramic particles with a particle size of 1.5 mm are mixed with a binder, an activator, and paraffin particles in proportion to form a mixture;

[0129] Step 2: placing the mixture stirred in step 1 in a ceramic prefabricated block mold for pressing, then placing the mold in a resistance furnace, heating it to 120° C., demolding it after 2 hours, and then sintering it at a high temperature of 1250° C. for 12 hours to make it undergo a phase change, and naturally cooling it to room temperature to obtain a ceramic prefabricated block with a porous structure;

[0130] Step 3: Place the ceramic prefabricated block in the formed membrane shell, preheat it to 450-850°C, and then place the preheated membrane shell in a vacuum furnace;

[0131] Step 4: heating the iron-based alloy to 1535° C. to melt and form a high-temperature iron-based alloy liquid, and pouring the liquid into the membrane shell of the vacuum furnace, closing the sealing cover of the vacuum furnace to keep it in a closed state, and starting the vacuum pump to evacuate the air in the vacuum furnace to a vacuum state, so that the air in the pores of the ceramic prefabricated block is evacuated, thereby allowing the iron-based alloy liquid to infiltrate the pores of the ceramic prefabricated body, and then cooling to room temperature after keeping the temperature for 20 hours to obtain the composite reinforced wear-resistant material of the present invention;

[0132] The iron-based alloy includes the following raw materials in parts by weight: 3.0 parts of C, 20 parts of Cr, 72.5 parts of Fe, 1.8 parts of Mo, and 1.7 parts of V.

[0133] The ratio of the ceramic particles to the binder, activator, and paraffin particles in this embodiment is 10:2.5:2:1; the activator is silicon carbide powder; and the binder is an inorganic binder;

[0134] The porosity of the ceramic prefabricated block with a porous structure is 38.5%; the membrane shell preheated for molding is made of metal heat-resistant steel.

[0135] The composite reinforced wear-resistant material of this embodiment also includes 11 parts of reinforcing agent; the reinforcing agent is used for reinforcing and improving the iron-based alloy;

[0136] The preparation method of the enhancer is as follows:

[0137] S01: yttrium oxide is first placed in a proton irradiation box for irradiation for 7.5 minutes, the irradiation power is 350W, and then preheated at 58°C for 12.5 minutes. Preheating is completed to obtain a preheated yttrium oxide body;

[0138] S02: 3 parts of silane coupling agent KH550, 2 parts of chitosan solution with a mass fraction of 3.5% and 5.5 parts of sodium dodecylbenzene sulfonate solution were mixed thoroughly;

[0139] Then, 4 parts of preheated yttrium oxide and 3 parts of B powder were added, and the blending and ball milling treatment was continued. The ball milling speed was 1500r / min, and the ball milling was performed for 2h. After the ball milling was completed, a yttrium oxide-based modifier was obtained.

[0140] S03: Si powder is first placed in a dopamine hydrochloride solution of 4 times the total amount of Si powder, and then carboxymethyl cellulose of 6.5% of the total amount of Si powder is added and mixed thoroughly to obtain a regulator;

[0141] S04: The regulator and the yttrium oxide-based modifier are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water and dried to obtain a reinforcing agent.

[0142] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 4.5%; the mass fraction of the dopamine hydrochloride solution is 5.5%.

[0143] The particle size of the B powder in this embodiment is 12.5 um; the particle size of the Si powder is 3.5 um; the stirring speed of the stirring modification treatment is 500 r / min, and the stirring time is 35 min.

[0144] The preparation method of the iron-based alloy of this embodiment is:

[0145] The alloy containing C, Cr, Fe, Mo, V and the reinforcing agent are sequentially added into the smelting furnace for smelting to form an iron-based alloy melt, which is then cast into a mold, cooled and formed, and then demolded to obtain an iron-based alloy ingot.

[0146] The ceramic particles of this embodiment are also treated by ultrasonic immersion of the modifier;

[0147] The preparation method of the modifier is:

[0148] S11: immersing the silicon carbide whiskers into a 5% lanthanum nitrate solution having a mass fraction of 4 times the total amount of the silicon carbide whiskers;

[0149] Then, 6.5% of the total amount of silicon carbide whiskers was added with silane coupling agent KH560, and the mixture was immersed and stirred sufficiently. The immersion speed was 600 r / min, and the immersion time was 30 min. After the immersion was completed, a lanthanum-doped whisker solution was obtained.

[0150] S12: 3.5 parts of hydroxyapatite, 2 parts of flake graphene, 4.5 parts of sodium lignin sulfonate solution, 2 parts of citric acid and 0.60 parts of nano-silica sol are mixed and ball-milled at a ball-milling speed of 1250 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified additive;

[0151] S13: The lanthanum-doped whisker liquid and the modifying additive are mixed in a weight ratio of 7:3 to obtain a modifying agent.

[0152] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 3.5%;

[0153] The immersion power of the ultrasonic immersion treatment in this embodiment is 370W, and the immersion time is 25min;

[0154] The composite reinforced wear-resistant material prepared by the method for preparing an iron-based ceramic composite reinforced wear-resistant material by a vacuum infiltration method in this embodiment.

[0155] Comparative Example 1.

[0156] The difference from Example 3 is that no reinforcing agent is added to the iron-based alloy.

[0157] Comparative Example 2.

[0158] The difference from Example 3 is that no regulator is added during the preparation of the enhancer.

[0159] Comparative Example 3.

[0160] The difference from Example 3 is that the regulator is replaced by Si powder.

[0161] Comparative Example 4.

[0162] The difference from Example 3 is that no yttrium oxide-based modifier is added to the reinforcing agent.

[0163] Comparative Example 5.

[0164] The difference from Example 3 is that no preheated yttrium oxide body is added in the preparation of the yttrium oxide-based modifier.

[0165] Comparative Example 6.

[0166] The difference from Example 3 is that B powder and silane coupling agent KH550 were not added in the preparation of the yttrium oxide-based modifier.

[0167] Comparative Example 7.

[0168] The difference from Example 3 is that the ceramic particles are not treated with a modifier.

[0169] Comparative Example 8.

[0170] The difference from Example 3 is that no modifying additive is added to the modifier.

[0171] Comparative Example 9.

[0172] The difference from Example 3 is that no silicon carbide whiskers are added to the lanthanum-doped whisker liquid.

[0173] Comparative Example 10.

[0174] The difference from Example 3 is that the preparation method of the modifier is different:

[0175] 3.5 parts of hydroxyapatite, 2 parts of flaky graphene, 4.5 parts of sodium lignin sulfonate solution, 2 parts of citric acid and 0.65 parts of nano-silica sol were fully ball-milled at a ball-milling speed of 1250 r / min for 2 hours to obtain a modifier.

[0176] The strength, toughness and wear resistance of the products of Examples 1 to 3 and Comparative Examples 1 to 10 were tested, and the test results are as follows:

[0177]

[0178]

[0179] It can be seen from Comparative Examples 1 to 10 and Examples 1 to 3 that;

[0180] The product of Example 3 has excellent fracture toughness, as well as excellent bending strength and wear resistance, and the three can be improved in a coordinated manner. The product performance of Example 3 is superior to the product performance of Comparative Examples 1-10.

[0181] The product was placed in 2% hydrochloric acid mist for 1 hour, then placed at 120°C with an impact strength of 10Mp for 5 minutes, and then at -5°C with an impact strength of 10Mp for 5 minutes. The above test is one cycle, and a total of 10 cycles were performed to test the corrosion resistance and thermal shock resistance of the product. The test results are as follows

[0182]

[0183]

[0184] It can be seen from Comparative Examples 1 to 10 and Example 3 that

[0185] Without adding reinforcing agent to iron-based alloy and without using modifier to treat ceramic particles, the performance of the product has a significant trend of deterioration. The synergistic effect of the two is the most significant.

[0186] In the preparation of the reinforcing agent, no regulator was added for treatment, the regulator was replaced by Si powder, no yttrium oxide-based modifier was added to the reinforcing agent, no preheated yttrium oxide body was added in the preparation of the yttrium oxide-based modifier, and no B powder and silane coupling agent KH550 were added in the preparation of the yttrium oxide-based modifier. The performance of the products showed a trend of deterioration to varying degrees. The product performance effect was most significant when the regulator obtained by the method of the present invention was used in combination with the yttrium oxide-based modifier obtained by the method of the present invention. The effects of other methods were not as obvious as those of the present invention.

[0187] When no modifying additive is added to the modifier, no silicon carbide whisker is added to the lanthanum-doped whisker liquid, and the preparation methods of the modifier are different, the performance of the product tends to deteriorate. When no modifying additive is added, the performance of the product tends to deteriorate significantly. The modifier obtained by the method of the present invention has the most significant product performance effect.

[0188] Since the modified additives have a significant impact on the performance of the product, further research is needed:

[0189] 3.5 parts of hydroxyapatite, 2 parts of flake graphene, 4.5 parts of sodium lignin sulfonate solution, 2 parts of citric acid and 0.65 parts of nano-silica sol were fully blended and ball-milled at a ball-milling speed of 1250 r / min for 2 hours. After the ball-milling was completed, the mixture was washed with water and dried to obtain a modified additive.

[0190] Experimental example 1.

[0191] The only difference from Example 3 is that hydroxyapatite is not added to the modified additive.

[0192] Experimental example 2.

[0193] The only difference from Example 3 is that no flake graphene is added to the modifying additive.

[0194] Experimental Example 3.

[0195] The only difference from Example 3 is that the sodium lignin sulfonate solution is replaced by deionized water.

[0196] Experimental Example 4.

[0197] The only difference from Example 3 is that citric acid and nano-silica sol are not added to the modified additive.

[0198] Based on the corrosion resistance and thermal shock resistance tests, the performance of product experimental examples 1-4 was continued to be tested as follows:

[0199]

[0200] It can be seen from Experimental Examples 1-4 that no flaky graphene is added to the modifying additive, and the performance of the product is most affected by the modifying additive, followed by the fact that no hydroxyapatite is added. At the same time, the sodium lignin sulfonate solution in the product is replaced by deionized water, and citric acid and nano-silica sol are not added to the modifying additive. The performance of the product tends to deteriorate. The modified additive obtained by combining citric acid, sodium lignin sulfonate solution and nano-silica sol with hydroxyapatite and flaky graphene, and by the mutual coordination and synergy between the raw materials, has the most significant effect on the product performance. The raw materials in the modifying additive are indispensable, and the use of other methods to replace them is not as significant as the effect of the present invention.

[0201] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0202] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing an iron-based ceramic composite reinforced wear-resistant material by vacuum infiltration, characterized in that: The following steps are involved: Step 1: Ceramic particles with a particle size of 0.8-2.2 mm, a binder, an activator, and paraffin particles are mixed and stirred in proportion to form a mixture; Step 2: placing the mixture stirred in step 1 in a ceramic prefabricated block mold for pressing, then placing the mold in a resistance furnace, heating it to 120° C., demolding it after 2 hours, and then sintering it at a high temperature of 1250° C. for 12 hours to make it undergo a phase change, and naturally cooling it to room temperature to obtain a ceramic prefabricated block with a porous structure; Step 3: Place the ceramic prefabricated block in the formed membrane shell, preheat it to 450-850°C, and then place the preheated membrane shell in a vacuum furnace; Step 4: heating the iron-based alloy to 1520-1550° C., melting to form a high-temperature iron-based alloy liquid, and pouring it into the membrane shell of the vacuum furnace, closing the sealing cover of the vacuum furnace to keep it in a closed state, and starting the vacuum pump to evacuate the air in the vacuum furnace to a vacuum state, so that the air in the pores of the ceramic prefabricated block is evacuated, thereby allowing the iron-based alloy liquid to infiltrate the pores of the ceramic prefabricated body, keeping the temperature for 16-24 hours, and then cooling to room temperature to obtain the composite reinforced wear-resistant material of the present invention; The iron-based alloy comprises the following raw materials in parts by weight: 2-3.5 parts of C, 10-30 parts of Cr, 70-75 parts of Fe, 1.5-2 parts of Mo, and 1.5-2 parts of V.

2. The method for preparing an iron-based ceramic composite reinforced wear-resistant material by vacuum infiltration according to claim 1, characterized in that: The ratio of the ceramic particles to the binder, activator and paraffin particles is (8-11):(2-3):(1-3):1; wherein the activator is one of aluminum powder, silicon carbide powder and tungsten carbide powder; and the binder is an inorganic binder; The porosity of the ceramic prefabricated block with a porous structure is 35-60%; the membrane shell preheated for molding is made of metal heat-resistant steel.

3. The method for preparing an iron-based ceramic composite reinforced wear-resistant material by vacuum infiltration according to claim 1, characterized in that: The composite reinforced wear-resistant material also includes 8-13 parts of a reinforcing agent; the reinforcing agent is used for reinforcing and improving the iron-based alloy; The preparation method of the enhancer is as follows: S01: irradiate the yttrium oxide in a proton irradiation box for 5-10 minutes at a power of 350W. After the irradiation is completed, preheat the yttrium oxide at 55-60°C for 10-15 minutes to obtain a preheated yttrium oxide body. S02: Blend 2-4 parts of silane coupling agent KH550, 1-3 parts of chitosan solution with a mass fraction of 2-5%, and 4-7 parts of sodium dodecylbenzene sulfonate solution thoroughly; Then, 3-5 parts of preheated yttrium oxide and 2-4 parts of B powder are added, and the blending and ball milling treatment is continued. The ball milling speed is 1500r / min, and the ball milling is performed for 2h. After the ball milling is completed, a yttrium oxide-based modifier is obtained; S03: placing Si powder in a dopamine hydrochloride solution with an amount of 3-5 times the total amount of Si powder, and then adding carboxymethyl cellulose with an amount of 5-8% of the total amount of Si powder and blending them thoroughly to obtain a regulator; S04: The regulator and the yttrium oxide-based modifier are stirred and modified in a weight ratio of 2:

5. After the stirring is completed, the mixture is washed with water and dried to obtain a reinforcing agent.

4. The method for preparing an iron-based ceramic composite reinforced wear-resistant material by vacuum infiltration according to claim 3, characterized in that: The mass fraction of the sodium dodecylbenzenesulfonate solution is 3-6%; the mass fraction of the dopamine hydrochloride solution is 4-7%.

5. The method for preparing an iron-based ceramic composite reinforced wear-resistant material by vacuum infiltration according to claim 3, characterized in that: The particle size of the B powder is 10-15um; the particle size of the Si powder is 2-5um; the stirring speed of the stirring modification treatment is 450-550r / min, and the stirring time is 30-40min.

6. The method for preparing an iron-based ceramic composite reinforced wear-resistant material by vacuum infiltration according to claim 3, characterized in that: The preparation method of the iron-based alloy is: The alloy containing C, Cr, Fe, Mo, V and the reinforcing agent are sequentially added into the smelting furnace for smelting to form an iron-based alloy melt, which is then cast into a mold, cooled and formed, and then demolded to obtain an iron-based alloy ingot.

7. The method for preparing an iron-based ceramic composite reinforced wear-resistant material by vacuum infiltration according to claim 1, characterized in that: The ceramic particles are also treated by ultrasonic immersion of a modifier; The preparation method of the modifier is: S11: immersing the silicon carbide whiskers into a lanthanum nitrate solution having a mass fraction of 4-6% and a value 3-5 times the total amount of the silicon carbide whiskers; Then, 5-8% of the total amount of silicon carbide whiskers is added with silane coupling agent KH560, and the mixture is immersed and stirred sufficiently. The immersion speed is 550-750 r / min, and the immersion time is 30 min. After the immersion is completed, a lanthanum-doped whisker liquid is obtained; S12: 2-5 parts of hydroxyapatite, 1-3 parts of flake graphene, 3-6 parts of sodium lignin sulfonate solution, 1-3 parts of citric acid and 0.50-0.75 parts of nano-silica sol are mixed and ball-milled at a speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modified additive; S13: The lanthanum-doped whisker liquid and the modifying additive are mixed in a weight ratio of 7:3 to obtain a modifying agent.

8. The method for preparing an iron-based ceramic composite reinforced wear-resistant material by vacuum infiltration according to claim 7, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 2-5%.

9. The method for preparing an iron-based ceramic composite reinforced wear-resistant material by vacuum infiltration according to claim 7, characterized in that: The immersion power of the ultrasonic immersion treatment is 350-400W, and the immersion time is 20-30min.

10. A composite reinforced wear-resistant material prepared by the method for preparing an iron-based ceramic composite reinforced wear-resistant material by vacuum infiltration method as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-strength high-wear resistance high-temperature self-lubricating composite material and preparation method thereof

    CN103834866A

  • Ceramic-metal composite material based on binder jet printing and preparation method thereof

    CN116516209A

  • Method for manufacturing iron-based alloy ceramic composite wear-resistant material through high-temperature and high-pressure die casting method

    CN116532631A

  • Ordered heterostructure multi-metal composite material and preparation method thereof

    CN117340274A

  • High-performance powder coating for aluminum carriage of light truck and preparation method of high-performance powder coating

    CN118308014A

Cited By

  • Environment-friendly ceramic and preparation method thereof

    CN120965358A